Role of Genetic Variability Present in Germplasm for The Development of High-Yielding Maize Hybrids - Ghani, Aamir; Saeed, Muhammad; Malhi, Ahsan Raza; Shehzad, Aamar; Farooq, Umer; Murtaza, Ghulam; Ibrar, Iqra; Razaq, Abdul; Sami, Muhammad Usman; Rehman, Zia Ur (Biological and Clinical Sciences Research Journal, 2025)
The exploitation of genetic variability in maize germplasm is essential for the development of high-yielding, stress-resilient hybrids that meet the demands of diverse agroecological conditions. In Pakistan’s semi-arid regions, where environmental stresses challenge crop productivity, systematic evaluation of indigenous and multinational maize hybrids is crucial for sustainable agricultural advancement. Objective: To assess the genetic diversity and agronomic performance of indigenous and multinational maize hybrids through morphological, yield-related, and biochemical traits for hybrid development in semi-arid conditions. Methods: This experimental study was conducted at the Maize and Millets Research Institute, Yusafwala-Sahiwal, during the spring of 2024. A total of 70 maize hybrids (58 indigenous and 12 multinational) were evaluated in a randomized complete block design (RCBD) with three replications. Data were collected for days to tasseling and silking, plant height, ear height, cob length, thousand grain weight, protein content, fresh cob weight, and grain yield. Statistical analyses included analysis of variance (ANOVA) for trait differentiation, Pearson’s correlation analysis to determine inter-trait associations, and principal component analysis (PCA) to assess genetic diversity and trait contribution to yield variability. Results: ANOVA revealed significant genotypic differences (P < 0.05) for most traits. Grain yield showed a perfect positive correlation with fresh cob weight (r = 1.00), and moderate correlations with ear height (r = 0.70) and plant height (r = 0.36). PCA indicated that the first two principal components accounted for 53.06% of total variance, identifying fresh cob weight, grain yield, and plant structural characteristics as primary contributors to genetic diversity. Multinational hybrids achieved higher yields (>7,000 kg/ha), while select indigenous hybrids exhibited comparable performance, indicating their breeding potential. Conclusion: The study demonstrates the substantial genetic variability within maize germplasm and emphasizes the utility of multivariate statistical tools for hybrid selection. The competitive performance of certain indigenous hybrids highlights their strategic role in future breeding efforts aimed at enhancing maize productivity and resilience under semi-arid climates.